التحرّي عن ظاهرة تسطح الأفرع في حقول التفاح في مرتفعات الساحل السوري - مخول جرجس; إسماعيل عماد (Latakia University Journal -Biological Sciences Series, 2019)
بهدف التحّري عن ظاهرة تسطّح أفرع التفاح نُفّذت جولات حقلية خلال 2006-2008 لرصد هذه الظاهرة في حقول التفاح في الساحل السوري. أكدت نتائج الدراسة المسحية انتشار ظاهرة تسطّح الأفرع في حقول التفاح في مرتفعات الساحل السوري، وتزايد نسبة الانتشار. بلغت نسبة أشجار التفاح الحاملة لظاهرة التسطّح 12.47% بالنسبة للصنف غولدن ديليشيس و 15.97% بالنسبة للصنف ستاركنغ ديليشيس عامي 2006 و2008 على التوالي. تنتشر هذه الظاهرة في بشكل يسترعي الانتباه على أشجار التفاح في بساتين محافظة اللاذقية. كما سُجّل انتشار ظاهرة تسطّح الأفرع على أشجار أخرى مثل الخوخ، الكيوي، الكاكي، الرمان، وهو أول تسجيل لتسطّح أفرع هذه العوائل. Several missions were conducted during 2006-2008 in order to survey "Apple flat limb" phenomenon in apple orchards in the Syrian coastal heights. The results have proved the distribution of apple flat limb phenomenon in the surveyed apple orchards with increasing percentage of Golden delicious trees showing flat limb phenomenon (12.47% during 2006; and 15.97% during 2008). This phenomenon is dispersing on apple trees in Lattakia province orchards in a way that the warning should be seriously taken. The "flat limb’ phenomenon has been recorded on other tree species; Kiwi, Kaki, Plums and Pomegranate. This is the first record of such hosts for "flat limb’ phenomenon.